Gadolinium-complexed Aβ-binding contrast agents for MRI diagnosis of Alzheimer's Disease. (October 2015) - Matharu, Balpreet; Spencer, Nick; Howe, Franklyn; Austen, Brian
Abstract: MRI contrast agents, containing peptide sequences that bind β-amyloid and gadolinium ions ligated to DOTA have been synthesized for evaluation in early diagnosis of Alzheimer's Disease in transgenic mice models. A number of brain penetration modifications were incorporated and sufficient amounts of contrast agent in the brain were achieved only by addition of a cationic cell penetration sequence along with the use of microparticle assisted ultrasound activation. In the T1 mode of a MRI scan, the peptide (R2) illuminated areas of brain rich in amyloid plaques. Graphical abstract: